Canine Butterfly Glioblastomas: A Neuroradiological Review - Rossmeisl, John H.; Clapp, Kemba; Pancotto, Theresa E.; Emch, Samantha; Robertson, John L.; Debinski, Waldemar (Frontiers in Veterinary Science, 2016)
In humans, high-grade gliomas may infiltrate across the corpus callosum resulting in bihemispheric lesions that may have symmetrical, winged-like appearances. This particular tumor manifestation has been coined a ‘butterfly’ glioma (BG). While canine and human gliomas share many neuroradiological and pathological features, the BG morphology has not been previously reported in dogs. Here we describe the magnetic resonance imaging (MRI) characteristics of BG in three dogs, and review the potential differential diagnoses based on neuroimaging findings. All dogs presented with generalized seizures and interictal neurological deficits referable to multifocal or diffuse forebrain disease. MRI examinations revealed asymmetrical (2/3) or symmetrical (1/3), bihemispheric intra-axial mass lesions that predominantly affected the frontoparietal lobes and associated with extensive perilesional edema, and involvement of the corpus callosum. The masses displayed heterogeneous T1, T2, and FLAIR signal intensities, variable contrast enhancement (2/3), and mass effect. All tumors demonstrated classical histopathological features of glioblastoma (GBM) including glial cell pseudopalisading, serpentine necrosis, microvascular proliferation, as well as invasion of the corpus callosum by neoplastic astrocytes. Although rare, GBM should be considered a differential diagnosis in dogs with MRI evidence of asymmetric or symmetric bilateral, intra-axial cerebral mass lesions with signal characteristics compatible with glioma.